Collecting Robust Real-Time High Frequency Price Data in Fragile Settings - Pape, Utz J.; Nunez Chaim, Gonzalo I. (World Bank, Washington, DC, 2019)
To embark on a sustainable pathway toward development, effective policy responses must be implemented quickly and based on evidence. This requires reliable, timely data, which is often unavailable especially in fragile settings. An innovative High Frequency Survey (HFS) infrastructure offers a modern data collection system to fill critical data gaps. It can provide quantitative data to inform programs and policies, often linked to resilience in fragile settings. Using the cases of Somalia and South Sudan, this note describes the design and setup of such a HFS infrastructure and illustrates how high frequency price data can effectively support decision-making even in the event of an economic or humanitarian crisis.